2015
DOI: 10.1177/0145721715577484
|View full text |Cite
|
Sign up to set email alerts
|

Successful Patient Diabetes Education in the Emergency Department

Abstract: Study results provide evidence supporting the effectiveness of learner-centered DSME delivered in the ED at imparting critical knowledge and skills to patients with T2DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…The finding is in agreement with Abdo and Mohamed (2010) [36] in Egypt and Borhani et al (2015) [37] in Iran, who reported a similar success of an educational intervention for T2DM patients. Also in line with the current study results, Lewis et al (2015) [38] in a study in the United States revealed a retention of the post-intervention improvement in patients' knowledge at follow-up testing.…”
Section: Discussionsupporting
confidence: 91%
“…The finding is in agreement with Abdo and Mohamed (2010) [36] in Egypt and Borhani et al (2015) [37] in Iran, who reported a similar success of an educational intervention for T2DM patients. Also in line with the current study results, Lewis et al (2015) [38] in a study in the United States revealed a retention of the post-intervention improvement in patients' knowledge at follow-up testing.…”
Section: Discussionsupporting
confidence: 91%
“…DSME begins with a diagnosis from a primary care provider, yet 28% of patients diagnosed with diabetes have no provider. [30] A recent randomized controlled trial by Lewis et al concluded that learner-centered DSME presented in the ED can be effective with uncontrolled type 2 diabetic patients. [30] Other innovative techniques such as automated mobile health programs have been developed to help bridge the gap of underserved diabetic populations.…”
Section: Discussionmentioning
confidence: 99%
“…[30] A recent randomized controlled trial by Lewis et al concluded that learner-centered DSME presented in the ED can be effective with uncontrolled type 2 diabetic patients. [30] Other innovative techniques such as automated mobile health programs have been developed to help bridge the gap of underserved diabetic populations. [31,32] Arora et al found that while text messages did not statistically improve Hb A1c, it did improve medication adherence, and healthy behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Inpatient diabetes education is intended to deliver the critical survival skills required for safe self-care during the transition from the hospital to the ambulatory setting (Powers et al, 2015). To address the need for sustainable diabetes survival skills education (DSSE) for use in both inpatient and ambulatory settings, we have developed Diabetes to Go (D2Go), a DSSE program that assesses individual diabetes knowledge gaps and links those gaps to educational content (Lewis, Benda, Nassar, & Magee, 2015;Magee et al, 2013;Magee, Khan, Desale, & Nassar, 2014). D2Go has demonstrated effectiveness when provided to general medicine and surgery inpatients and in outpatient settings when delivered in a research context by a study team (Magee et al, 2013;Magee et al, 2014).…”
Section: Introductionmentioning
confidence: 99%